Pengaruh Kebijakan Modal Kerja terhadap Profitabilitas dan Nilai Perusahaan yang Terdaftar pada Jakarta Islamic Index - Andzar Izzurrahman; Mochamad Edman Syarief; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
In this study, working capital policies measured by Working Capital Investment Policy (WCIP) and Working Capital Financing Policy (WCFP) affect the corporate performance (profitability and goodwill) of nine companies included in the Jakarta Islamic Index (JII). We are investigating the impact. Listed during the period 2014-2020. The analysis tool used is a descriptive statistical and path analysis method using the software program WarpPLS 7.0. The data used is obtained in the form of secondary data from the website www.idx.com and also refers to literature and references to previous studies. As a result, investment policy (WCIP) did not affect profitability, and financing policy (WCFP) did affect profitability, but profitability itself did not affect goodwill. Partially investment and financing policies (WCFP) affected goodwill. .. This study focuses on the company's current assets and liabilities, as it focuses on the working capital policy that the company uses to carry out its business.